Pengaruh Kecepatan Udara Terhadap Kerja Reaktor Bubble Fluidized Bed Gasifire - Sukarno, Ganet Rosyadi (2016)
Rice husk biomass is a renewable energy source and potential in Indonesia. Through a fluidized bed reactor technology bubble gasifire, burnt rice husk with limited oxygen to produce methane gas that can be directly burned. Rice husk gasification testing aims to determine the effect of air velocity on the combustion temperature, effective flame and combustion efficiency. This study begins by setting the air from the compressor to the gasifier, the air then varied the speed. Air speed used was 3.5 m / s, 4 m / s and 4.5 m / s, then measured the temperature of combustion every 2 minutes with 4 points thermocouple attached. The results showed variations in airspeed affects the combustion temperature, effective flame and furnace efficiency. In the air velocity 3.5 m / s generates an average temperature of combustion at 1620C, effective flame for 80 minutes, and amounted to 22.63% efficiency furnace. Air velocity 4 m / s highest combustion temperature of 3060C, effective flame for 90 minutes and furnace efficiency by 9.77%. Speed of 4.5 m / s the highest combustion temperature of 2650C, effective flame for 126 minutes and an efficiency of 7.04%.